Centaur - Wrenn, Greg (Book collections on Project MUSE., 2013)
The poet's debut collection opens with a long poem in which a man undergoes surgery to become a centaur. Other poems speak in voices as varied as those of Robert Mapplethorpe, Hercules, and a Wise Man at the birth of Jesus. This collection explores the blurred lines between compulsivity and following one's heart, stasis and self-realization, human and animal. Here, suffering and transcendence are conjoined.